Growth of L-asparagine monohydrate organic single crystals: An experimental and DFT computational approach for nonlinear optical applications - Md Anisur Rahman; Jiban Podder (Heliyon)
Good optical quality of L-asparagine monohydrate (C4H8N2O3.H2O) organic single crystal has been grown by adopting natural slow evaporation process at room temperature from aqueous solutions. The lattice parameters obtained by powder X-ray diffraction data revealed orthorhombic crystal system of the harvested crystal. The morphology and planes of the crystal have been identified. The molecular vibrations and functional groups have been specified by Fourier transform infrared (FTIR) spectroscopy studies. Energy dispersive X-ray (EDX) study has been availed to find out the elements constituting the crystal. Scanning electron microscopy, (SEM), provided the surface morphology of the crystal. The dependence of dielectric properties on frequency and temperature have been investigated and the electronic polarizability (α) has been determined. UV–vis spectral analysis shows that the crystal possesses good optical transmittance in the visible part of the energy spectrum. The optical band gap and the Urbach energy have been determined from lower absorption edge. Third order nonlinear susceptibility χ(3), nonlinear refractive index (n2), and linear susceptibility χ(1) have been calculated by Miller's generalized rule. The first-principle computation of band structure of electrons and the electron density of states have been discussed, which suggest that the crystals possess direct band gap. Density Functional Theory (DFT) with B3LYP function by Gaussian09W software was utilized to calculate HOMO-LUMO energy gap as well as non-linear optical parameters namely, linear polarizability (α), hyperpolarizability (β and γ) and dipole moment (μ) of L-asparagine monohydrate crystal. All the findings prove that L-asparagine monohydrate is a promising NLO crystal.